Development of Project-Based Physics Teaching Modules to Improve Students’ Science Process Skills - Nur Hijrah Muthmainnah R; Kaharuddin Arafah; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2026)
This study is a type of research and development (R&D). The research was conducted by the Four-D models. This study consisted of four stages, namely needs analysis (analyze), product design (design), product development (development), and product dissemination (dissemination). The purpose of this research was to produce a project-based physics teaching module to improve students' science process skills that meet the criteria of validity, practicality, and effectiveness. The project-based physics teaching module was validated by three experts. The test subjects were Grade XI students of State Senior High School 13 Takalar in the 2025/2026 academic year. The results of the study indicate that expert assessments of the developed physics teaching module were analyzed using the Aiken's V index, with an average content feasibility score of 0.78, a presentation feasibility score of 0.76, and a graphic feasibility score of 0.78 in the moderate category. Meanwhile, the language feasibility score was 0.82 in the high category. The results of the expert judgment of the project-based teaching module yielded a cumulative response score of 87.33%, categorized as very practical. The implementation observation results yielded a cumulative score of 81.30%, categorized as practical. Therefore, the project-based physics teaching module was considered feasible for implementation and use. The effectiveness of the project-based physics teaching module was determined based on the pre-test and post-test results of students' science process skills, which were analyzed using the N-gain test. Overall, the average N-gain score of students was 0.68, categorized as moderate. It can be concluded that there was an improvement in the science process skills of Grade XI students of State Senior High School 13 Takalar through the use of the project-based physics teaching module. This indicates that the project-based physics teaching module is effective for physics learning.